PRESENT UNDERSTANDING OF ACEH TSUNAMI (APPLICATIONS OF DATA FROM FIELD TO SATELLITE OBSERVATIONS) - I Gede Hendrawan; Bambang Sukresno; Yasuhiro Sugimori (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2007)
Application of data from field to satellite observation and simulation has been made as present understanding of Aceh tsunami. Tsunami has attracted attention after struck Aceh in December 26th 2004, generated by a strong eartquake with magnitude Mw=9.0. The eatrhquake triggered giant tsunami waves that propagated throughout the Indian Ocean, causing extreme inundation and destruction along the northern and western coast of Sumatra. Within hours, the tsunami devastated the distant shores of Thailand to east as well as Sri Lanka, India and Maldives to the west. The tsunami also caused deaths, and destruction in Somalia and other nations of East Africa. The tsunami was recorded on tidal stations throughout the Indian Oceans in worldwide. Unlike the Pacific, the Indian Ocean does not yet have a network of deep-ocean pressure sensors, and so coastal tide gauges provide the only direct measurement of Indian Ocean stunami amplitudes. We had many lessons and basic knowledge which had already been learned from this tragic event in the Indian Ocean. Many more lessons should be learned in the near future as this tragedy unfolds and reverals many failures to value and protect human life in this neglected region of the world. Keywords: Tsunami, Earthquake, Indian Ocean, Aceh.